2002
DOI: 10.1021/ja016741x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Monomeric MnIII/II−OH and MnIII−O Complexes from Water:  Evaluation of O−H Bond Dissociation Energies

Abstract: The syntheses and properties of the monomeric [MnIII/IIH31(OH)]-/2- and [MnIIIH31(O)]2- complexes are reported, where [H31]3- is the tripodal ligand tris[(N'-tert-butylureaylato)-N-ethyl)]aminato. Isotope-labeling studies with H218O confirmed that water is the source of the terminal oxo and oxygen in the hydroxo ligand. The molecular structures of the [MnIIH31(OH)]2- and [MnIIIH31(O)]2- complexes were determined by X-ray diffraction methods and show that each complex has trigonal bipyramidal coordination geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 20 publications
5
60
1
Order By: Relevance
“…Borovik has disclosed a compound with the backbone structure 4, which features an unusual non-bridging terminal hydroxo ligand, and has measured its pK a and redox properties ( Figure 7) [64][65][66]. In a preliminary study of 4 and its isomers, the Mn IV oxo was observed to abstract the hydrogen atom from TEMPO-H, cyclohexadiene, dihydroanthracene, 1,2-diphenyl hydrazine, and 2,4,6-tri-tertbutyl phenol.…”
Section: Metal-oxo Complexes For C-h Bond Oxidationmentioning
confidence: 99%
“…Borovik has disclosed a compound with the backbone structure 4, which features an unusual non-bridging terminal hydroxo ligand, and has measured its pK a and redox properties ( Figure 7) [64][65][66]. In a preliminary study of 4 and its isomers, the Mn IV oxo was observed to abstract the hydrogen atom from TEMPO-H, cyclohexadiene, dihydroanthracene, 1,2-diphenyl hydrazine, and 2,4,6-tri-tertbutyl phenol.…”
Section: Metal-oxo Complexes For C-h Bond Oxidationmentioning
confidence: 99%
“…Only a limited number of model Mn complexes having mononuclear (10,11) or binuclear manganese-oxo cores have contributed to understanding the kinetic steps in pcet chemistry (3,12). These and related studies led to different results with some systems following a pathway of initial H abstraction (3,13,14) [with large kinetic isotope effect (KIE) in the range of 30-40 (15)], in contrast to other cases that exhibited an electrochemical step followed by a proton-transfer step with minimal H͞D isotope effect (1,16).…”
mentioning
confidence: 99%
“…This HBDE is precisely the thermodynamic value necessary for Babcock's H-atom abstraction model (Gardner & Mayer 1995;Caudle & Pecoraro 1997). More recent work on a single set of compounds suggests that going higher than Mn IV leads to a large increase in the HBDE (Gupta et al 2002). Nonetheless, these studies demonstrated that PCET was thermodynamically important in the water-oxidation process.…”
Section: K1mentioning
confidence: 93%